An Adaptive Overcurrent Protection Scheme of Distribution Networks With DG Penetration - Muhammad Zul Helfi Azri Bin Abd Hadi (2023)
Due to the benefits of low pollution and high flexibility, installation of Distributed Generation in power system becomes more popular in recent years. However, despite these advantages, the integration of DG into the distribution system can cause a number of issue depending on the type and placement. The change in the network system may affect the traditional overcurrent protection relays. Thus, adaptive overcurrent protection is necessary to counter the issue and can be implemented by using a microprocessor-based overcurrent relay. In this thesis, a fast recursive discrete Fourier transform (FRDFT) algorithm is introduce into the overcurrent relay to ensure the relay detect accurate fault signal and sends a correct signal to circuit breaker. A radial 5 bus system is developed and used to validate the proposed adaptive scheme. The simulation result proves that the FRDFT algorithm is capable of providing accurate trip time of the circuit breaker.